APPLYING PEER FEEDBACK ON STUDENTS’ DESCRIPTIVE WRITING IN EFL CLASSROOM: A CLASSROOM ACTION RESEARCH AT ONE OF ISLAMIC SENIOR HIGH SCHOOL IN JAMBI - Khusnul Yatima; Yulia Wiji Astika; Sri Kadarsih (International Journal of Southeast Asia, 2020)
This study deals with a classroom action research investigating teaching descriptive writing through peer feedback in EFL classroom at one of Islamic Senior High School in Jambi. Eleven male students were involved in this research. By doing field note, observation checklist, writing task, and documentation data were collected and analyzed descriptively. The findings indicated that peer feedback could improve students’ descriptive writing seeing that the students were able to work collaboratively with the peer in giving either suggestion or advise during the discussion. As a result, applying peer feedback while teaching descriptive writing did not only provide students basic material for editing or revising, but also stimulate their imaginative power enabling them to have a concept in their mind about what they are going to write. Implications from this research evidently suggest that teachers should have a variety of teaching strategy in teaching English as a Foreign Language.